Combination Effects of Moringa oleifera Leaf Ethanol Extract and Andrographis paniculata Herb on Blood Glucose Levels and Pancreas Histopathology of Diabetic Rats Induced by Streptozotocin - Annisa Fatmawati; Moch. Saiful Bachri; Laela Hayu Nurani (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Type 2 diabetes mellitus is a non-contagious disease, can damage the glucose metabolic system in the body, and is characterized by hyperglycemic conditions. Moringa leaves (Moringa oleifera) and Andrographis herbs (Andrographis paniculata) have been studied to have antihyperglycemic activity in diabetic rats. The purpose of this study was to determine the effect of the combination of Moringa leaf ethanol extract (MLEE) and ethanol extract of Andrographis herbs (AHEE) in streptozotocin-induced rats (45 mg/kgBW). The subjects consisted of 32 rats, divided into 8 groups (1 healthy group and 7 type 2 DM groups). The study was conducted for 4 weeks by measuring blood glucose levels in pre-treatment, day 0, 14 and 28 with a single MLEE treatment dose of 300 mg/kgBW, single AHEE 300 mg/kgBW, combination of MLEE and AHEE 150+150 mg/kgBW, 200+100 mg/kgBW, 100 + 200 mg/kgBW, and gliclazide 5 mg/kgBW orally. The results of measurement of fasting blood glucose levels on day 28 showed that administration of gliclazide 5 mg/kg BW, single dose MLEE and AHEE, as well as its combination, had significant differences (p<0.05) compared to the hyperglycemic control group. Pancreatic organ histopathology features in the extract dose group showed that there was a change in the repair of insula Langerhans compared to the hyperglycemic control group which showed necrotic damage due to streptozotocin induction. Combination administration has the same antihyperglycemic effect by single dose extract in diabetic rats within 28 days, which also restore weight loss to normal.